Pengaruh Isi Pekerjaan dan Kepuasan Kerja Terhadap Kinerja Karyawan Di Hotel “Armani” Muara Teweh Kalimantan Tengah - Rusanita Rusanita; Emy Rahmawati; Setio Utomo (JURNAL BISNIS DAN PEMBANGUNAN, 2019)
The existence of inpatient services as a means of supporting business and industry in Muara Teweh North Barito Regency has progressed. Hotels in Muara Teweh North Barito Regency as many as 4 units, Hotel Armani Muara Teweh is the first hotel with starred facilities. With the existence of Armani hotel is able to help assist in terms of taxation, local employment and support in the world of tourism so as to facilitate the investors / businessmen to come to the town of Muara Teweh Central Kalimantan. This study aimed to examine the effect of Content Works (X1) and Job Satisfaction (X 2) the Employee Performance (Y) in "Armani" Central Kalimantan Muara Teweh either partially or simultaneously. Samples taken as many as 50 employees were selected with saturated sampling technique. Data collection using questionnaire while data analysis using SPSS program. The test results prove Fill Jobs significant effect on employee performance partially to great effect 5.529 and job satisfaction significantly influence employee performance partially to great effect 2,379 while simultaneously Fill Jobs and job satisfaction significantly influence employee performance with great influence 20.268 while the rest of 0.463 influenced by other variables Keywords: Job Content, Job Satisfaction, Employee Performance